COMPARISON OF LAPAROSCOPIC AND OPEN SURGERY FOR ACUTE CHOLECYSTITIS (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
Acute cholecystitis is a rapidly developing inflammatory disease of the gallbladder, and surgical treatment is the main method. This article discusses the clinical and practical comparison of laparoscopic and open cholecystectomy methods used in the treatment of acute cholecystitis. Laparoscopic surgery is characterized by minimal invasiveness, low postoperative pain, short hospital stay, and rapid rehabilitation. Open surgery is preferred in complex, complicated, or late-detected cases. The article analyzes the advantages and disadvantages of both methods, the duration of the operation, the risk of complications, and the impact on the patient's quality of life. The importance of an individual approach in modern surgical practice, depending on the patient's general condition and the severity of the disease, is substantiated.